2013
DOI: 10.1055/s-0032-1311646
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Outcomes of Transplanting Autologous Granulocyte Colony-stimulating Factor-mobilised Peripheral Mononuclear Cells in Diabetic Patients with Critical Limb Ischaemia

Abstract: The efficacy and safety of transplanting autologous mesenchymal stem cells (MSCs), from granulocyte-colony-stimulating factor (G-CSF)-mobilised peripheral blood, was investigated in diabetic patients with critical limb ischaemia (CLI). After 3 months, the transplanted group of patients (n=7) showed a significant improvement in ischaemia manifestations, including pain and neurological signs, wound healing and the rate of lower-limb amputation, compared to the control group of patients (n=14). Pain was significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 27 publications
0
51
0
Order By: Relevance
“…Following careful screening of titles and abstracts, 399 articles were excluded leaving 7 articles that fulfilled the predefined inclusion criteria and were included in the final analysis [20][21][22][23][24][25][26]. A total of 6 publications were full-text articles out the 7 studies [20,[22][23][24][25][26], whereas 1 publication was a meeting conference [21].…”
Section: Study Selectionmentioning
confidence: 99%
“…Following careful screening of titles and abstracts, 399 articles were excluded leaving 7 articles that fulfilled the predefined inclusion criteria and were included in the final analysis [20][21][22][23][24][25][26]. A total of 6 publications were full-text articles out the 7 studies [20,[22][23][24][25][26], whereas 1 publication was a meeting conference [21].…”
Section: Study Selectionmentioning
confidence: 99%
“…9094 One study reported significantly fewer patients facing major amputation of a limb in the group infused with PB-MNC versus those in the control group at the conclusion of the studied. 93 …”
Section: Trials Of Cell-based Therapiesmentioning
confidence: 99%
“…These include bone marrow and peripheral blood mononuclear cells [11][12][13][14][15][16][17], mesenchymal stem cells (MSCs) [18][19][20][21][22], cell lines selected based on the presence of specific markers [15,[23][24][25], adipose tissue-derived cells [26][27][28][29], and induced pluripotent stem cells-derived cells [30,31]. Each of these cell types has shown promise for the treatment of CLI in mechanistic and preclinical studies.…”
Section: Introductionsmentioning
confidence: 99%